Celebrity Endorsement and Involvement With the Social Cause in Nonprofit Organizations. Issue 4 (1st October 2016) - de los Salmones, Mª del Mar García; Dominguez, Rafael
ABSTRACT: Celebrity endorsement has become a very popular communication strategy in the nonprofit sector, although there are still doubts about its effectiveness. Specifically, one interesting question is whether the involvement of individuals with a social cause can explain differences in the valuation and effects of the celebrity endorsement strategy in consumer behavior. Taking into account this fact, the current research presents a causal model that analyzes the determinants of the attitude toward ads involving celebrities and the explanatory variables of the behavioral intentions in this sector. We worked with two subsamples of individuals with high and low involvement, who rated a fictitious ad with a well-known social entity and a celebrity. As a result, we observed that the strategy can influence the group of low involved people and have no significant effects on the segment with high involvement.